PENGGUNAAN METODE WEB ENGINEERING DALAM APLIKASI PENJUALAN KAIN KHAS PALEMBANG - Nyimas Sopiah; Eka Puji Agustina (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2018)
Palembang typical fabrics have many types. For example, jumputan fabric, Songket cloth and Tajung cloth. So far the marketing of typical Palembang fabrics is still done conventionally, namely with consumers coming to the house of the typical fabric craftsman to buy it. To market the typical fabric of Palembang, the sale of typical fabrics will be made online, so as not only to increase sales, but also to promote typical Palembang fabrics in the international world and also be able to support income for Palembang's fabric craftsmen. This sale can also increase turnover for small and medium businesses in the city of Palembang. Making applications using Web Engineering software development methods. While the programming language used to make this application is PHP (Personal Homepage).